Jigsaw Cooperative Learning and Its Impact on Students’ Motivation in Mathematics Education - Ari Wibowo; Nana Harlina Haruna; Andi Indra Sulestry; Achmad Salido (Jurnal Pedagogi dan Inovasi Pendidikan, 2025)
This study aimed to examine the effect of the jigsaw cooperative learning model on students’ motivation in mathematics learning. A quantitative approach with a pre-experimental design was employed. The population consisted of eighth-grade students, from which one class of 41 students was selected using purposive sampling. Data were collected using a mathematics learning motivation questionnaire. Descriptive statistics were used to describe students’ motivation levels, while inferential statistics using a t-test were applied to test the research hypothesis. The results showed that students’ motivation in mathematics learning before and after the implementation of the jigsaw cooperative learning model was generally at a moderate level. However, the implementation of the jigsaw model resulted in an increase of 80.48% in overall students’ motivation and a 96% increase across motivation indicators. The t-test results indicated that the calculated t-value (5.6774) exceeded the critical t-value (2.02), demonstrating a statistically significant effect of the jigsaw cooperative learning model on students’ motivation in mathematics learning. These findings suggest that the jigsaw cooperative learning model is an effective instructional strategy for enhancing students’ motivation in mathematics.